MITOS MASYARAKAT JAWA DALAM NOVEL CENTHINI: 40 MALAM MENGINTIP SANG PENGANTIN (KAJIAN ANTROPOLOGI SASTRA) - Kiki Astrea (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
Literary anthropology is the study of literature with human relevance.In this case anthropology discusses the myths that developed in human beings.Myth is a similar story with a fairy tale.Analysis of myths in the novel Centhini: 40 nights trying to find a peek at the bride myths that developed in the body of the Java community.Like the myth of the marriage, building a house until the myths associated with religion.The analysis of data has a corresponding meaning to the myth of literary anthropology.One conth data analysis, namely the myth of human destiny is determined by heredity, meaning that the fate of a person in accordance with the offspring, if the parents are kings and will he became king, if his parents were slaves then he will be a slave.